2000
DOI: 10.1111/j.1151-2916.2000.tb01381.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray Studies of Ferroelectric Cathodes

Abstract: Ferroelectric electron emission has two possible sources: rapid polarization switching and surface plasma discharge. The present paper uses an X-ray diffraction (XRD) method to support the theory of rapid polarization switching for lead zirconate titanate samples. A decrease in the 002 peak value and an increase in the 200 peak value were observed after electron emission in two types of samples, which were doped with lanthanum and neodymium. A comparison of the XRD data for the samples showed that a high-densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Shuren Zhang et al [4] reported the change in intensities of 002 and 200 peaks due to domain switching. The XRD intensity ratio I(002)/I(200) represents the ratio of volume of c-domains to that of a-domains on the PZT surface.…”
Section: Resultsmentioning
confidence: 98%
“…Shuren Zhang et al [4] reported the change in intensities of 002 and 200 peaks due to domain switching. The XRD intensity ratio I(002)/I(200) represents the ratio of volume of c-domains to that of a-domains on the PZT surface.…”
Section: Resultsmentioning
confidence: 98%
“…The difference between and the formula ( N =( R − R ′)/ R (1+ R ′)), which has been used previously to evaluate the degree of 90° domain reorientation of PZT system, 1,5,10 is that the | F 200 | 2 /| F 002 | 2 term is neglected in the latter formula.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this topic has been investigated by many researchers. Most attention so far has, however, been paid to the PZT (or PLZT) system, 1–5 and as such there are few published papers concerning the Pb(Mg 1/3 Nb 2/3 )O 3 –PbTiO 3 (PMN–PT system) 6,7 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations